2015
DOI: 10.1194/jlr.m057539
|View full text |Cite
|
Sign up to set email alerts
|

ORMDL/serine palmitoyltransferase stoichiometry determines effects of ORMDL3 expression on sphingolipid biosynthesis

Abstract: The ORM1 ( Saccharomyces cerevisiae )-like proteins (ORMDLs) and their yeast orthologs, the ORMs, regulate the initiating and rate-limiting enzyme in sphingolipid biosynthesis, serine palmitoyltransferase (SPT) ( 1-4 ). The three ORMDL isoforms (ORMDL1-3) are small (17.5 kDa) hydrophobic membrane proteins that are situated in the endoplasmic reticulum along with SPT. The three isoforms are highly homologous and their functions appear to be redundant at the cellular level ( 3, 4 ). The ORMDLs are negative regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 22 publications
(44 reference statements)
4
67
1
Order By: Relevance
“…These findings suggested that yeast ORM proteins are negative regulators of sphingolipid biosynthesis and act through the inhibition of SPT. This conclusion was later confirmed in other studies using cells of various origin, including rice (66), mice (67), and human cell lines (68)(69)(70)(71).…”
Section: -Ketodihydrosphinganine Reductasesupporting
confidence: 69%
See 4 more Smart Citations
“…These findings suggested that yeast ORM proteins are negative regulators of sphingolipid biosynthesis and act through the inhibition of SPT. This conclusion was later confirmed in other studies using cells of various origin, including rice (66), mice (67), and human cell lines (68)(69)(70)(71).…”
Section: -Ketodihydrosphinganine Reductasesupporting
confidence: 69%
“…Furthermore, when expression of all ORMDLs was decreased and ORMDL3 had been re-introduced, the production of ceramides was lowered in comparison with ORMDLs siRNA (67). This contradicts previous findings (68,70) and supports the theory that it is ORMDL3-mediated inhibition of sphingolipid metabolism that stays behind the ORMDL3-associated asthma phenotype. The levels of ORMDL proteins could also be regulated by the speed of their degradation.…”
Section: Ormdl Proteins In Mammalian Speciescontrasting
confidence: 56%
See 3 more Smart Citations